Fear of aging. Representations and imaginaries on elderly people in Argentina - Rada Schultze, Fernando (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
For just over a year, the world has been going through an unprecedented health crisis with an impact not only on health, but also on education, the economy, and work, among others. Likewise, this crisis in addition to generating new uncertainties and concerns regarding people's future, disrupted social relationships, daily life, and the way to define certain actors: old people began to be called a “risk group”. Thus, using the analysis of current statistics on the concerns of the Argentine population present in the media and public opinion, the article problematizes how they are related to representations, imaginaries, and stereotypes about old people, as well as how they can determine negative evaluations of older people.
Keywords: Representations; Imaginaries; Sociology of aging; Sociology of fear; Ageism